Effects of thyme (Thymus vulgaris), organic acid, probiotic and prebiotic on carcass characteristics and intestinal microbial population in broiler chickens fed with normal and low protein diets - Ahmadzadeh, A; Nobakht, A (Journal of the Hellenic Veterinary Medical Society, 2023)
The experiment was carried out to evaluate the effects of thyme, organic acid, probiotic and prebiotic on carcass characteristics and intestinal microbial microflora in broiler chicks in normal and low protein diets. A total of 388 Ross 308 broilers were equally assigned to 5 treatments with 4 replicates in a completely randomized design. The experimental treatments were; 1: control, 2: thyme extract (2 kg/ton), 3: organic acid (3 kg/ton), 4: probiotics (50 g/ton) and 5: prebiotics (2 kg/ton) with normal and reduced protein levels (10% lower than usual). At d 42, two chicks per replicate were randomly chosen, slaughtered and carcass percentage and carcass components percentage including a thigh, breast, liver, heart, gizzard, spleen, bursa of fabricius, abdominal fat, and intestine were determined for live weight. The results showed that using a diet with a normal level of crude protein compared to a diet with a level of crude protein lower than usual, increased the percentage of spleen and heart of chickens (P<0.05). It seems that there is a close relationship between the percentage of fat in the abdominal cavity and the ratio of energy to protein in the diet. Also, there were no significant differences between treatments and their interactions about pH content of ileum of broilers (P > 0.05). Besides, the bacterial population of ileum of treated broilers had different behavior. The ileum bacteria improved with probiotic addition and it was predictable because of beneficial bacteria inclusion to diet. Comparing the means for litter traits, no significant differences were observed between the experimental treatments with each other and with the control group (P>0.05). Totally, before the common use of additives in different types of diets of poultry nutrition, thorough investigations should be carried out on mechanisms, compatibility with other components of the diet and safety evaluation.